Wheat Stubble: What is its Value? - Kok, Hans; Wary, Joe; Kessen, Shelly (My University, 1997)
This publication describes the benefits of wheat stubble.
MF2240_1997_01
Keywords: MF2240; Crops; Environment and Natural Resources; MF